Breakfast on the Go - Jennifer Hillan; Claudia Peñuela (EDIS, 2010)
Revised! FCS8715, a 2-page fact sheet by Jennifer Hillan and Claudia Peñuela, compiles several 1-minute breakfast ideas, recipes for shakes and smoothies, and advice for healthier fast food breakfast choices. Published by the UF Department of Family, Youth and Community Sciences, October 2010.